El proceso laboral post pandemia y las reformas normativas pendientes - Quispe Montesinos, Carlos Alberto (2023)
The author begins the study by making a balance on the results of the implementation of the New Labor Procedural Law during its first years of enforcement. Then, the author analyzes the effects of the COVID-19 pandemic on labor lawsuits and the compatibility of the practices and experiences developed in response to it with the principles and content of our labor procedural model. Finally, the author proposes the reforms that should be considered in a forthcoming legislative modification of the law on the matter.